Using RELION software within the Scipion framework. Issue 4 (7th April 2021) - Sharov, Grigory; Morado, Dustin R.; Carroni, Marta; de la Rosa-Trevín, José Miguel
Abstract : An overview of the Scipion plugin for the RELION software package is presented and various image‐processing capabilities within the Scipion framework are discussed. Abstract : Scipion is a modular image‐processing framework that integrates several software packages under a unified interface while taking care of file formats and conversions. Here, new developments and capabilities of the Scipion plugin for the widely used RELION software package are presented and illustrated with an image‐processing pipeline for published data. The user interfaces of Scipion and RELION are compared and the key differences are highlighted, allowing this manuscript to be used as a guide for both new and experienced users of this software. Different on‐the‐fly image‐processing options are also discussed, demonstrating the flexibility of the Scipion framework.